The role of media policy in social networks and its challenges and perspectives - Abdrakhmanova, A.G.; Tapanova, S.E.; Toplu, M. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
Now is the time when everything is developing rapidly. Many things have been transformed within a short period of time. With the development of technology, people also began to change. A person who spends a lot of time on the Internet loses, first, itself. Mental health and attitude of the person to the surrounding world are changing too. The worst thing is that the person becomes addicted to the Internet, goes away from real life, and completely immerses himself in the world of the Internet. Therefore, we must not allow Internet addiction. Otherwise, we are risking shortening our already short life and turn it into meaningless existence. Television, the Internet, and social networks have been in the process of integration, that is, at the stage of involvement, for almost 15 years. The way of using them is for everyone’s personal matter; someone may correctly use Internet resources; others may abuse them. The Internet should be considered as a source of information, not as a competitor. The matter is that journalism is always in need of innovation. Kazakh ancestors said: Keep up with the times, that is, do not stay behind. So that, journalism should move with the times, taking a place on the front line. Only those media organizations that unite both sides may be a few steps ahead.